2020
DOI: 10.1097/md.0000000000019545
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transhepatic cholangiography versus endoscopic retrograde cholangiography for the pathological diagnosis of suspected malignant bile duct strictures

Abstract: To compare the diagnostic performance of percutaneous transhepatic cholangiography and endoscopic retrograde cholangiography for the pathological assessment of suspected malignant bile duct stricture, using brush cytology and forceps biopsy. The study group comprised 79 consecutive patients who underwent pathological assessment for suspected malignant biliary stricture, 38 of whom underwent percutaneous transhepatic cholangiography (group A) and the other 41 underwent endoscopic retrograde cholangio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…In a recent prospective randomized trial, liquid-based or smear cytology of EUS-FNA obtained from solid pancreatic masses reached a sensitivity of 88% and 83.8%, respectively, for the diagnosis of pancreatic cancer [ 28 ]. Brush cytology and forceps biopsies displayed an overall sensitivity of 77.1% for the diagnosis of suspected malignant biliary strictures when obtained by ERC(P) [ 29 ]. Our results are in line with the previous studies, which reported high sensitivity and specificity of bile cfDNA analysis in gallbladder cancer and cholangiocarcinoma [ 30 , 31 ] and showed its value as ancillary method in the diagnosis of malignant biliary strictures [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective randomized trial, liquid-based or smear cytology of EUS-FNA obtained from solid pancreatic masses reached a sensitivity of 88% and 83.8%, respectively, for the diagnosis of pancreatic cancer [ 28 ]. Brush cytology and forceps biopsies displayed an overall sensitivity of 77.1% for the diagnosis of suspected malignant biliary strictures when obtained by ERC(P) [ 29 ]. Our results are in line with the previous studies, which reported high sensitivity and specificity of bile cfDNA analysis in gallbladder cancer and cholangiocarcinoma [ 30 , 31 ] and showed its value as ancillary method in the diagnosis of malignant biliary strictures [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Браш-биопсия обладает меньшей чувствительностью и показателем точности. При цитологическом исследовании у большинства пациентов невозможно оценить дифференцировку опухолевого процесса из-за забора небольшого объема ткани [18][19][20]. В нашем центре после браш-биопсии высокодифференцированная аденокарцинома обнаружена в одном, умеренно дифференцированная -в двух случаях, что соста-вило лишь 12,5 %.…”
Section: Discussionunclassified
“…Число больных Браш-биопсия, % Щипцовая биопсия, % Комбинация, % Tapping (2012) [22] 31 87 94 -Boots (2017) [12] 129 40,6 42,7 55,8 Tibana (2019) [19] 18 -94,4 -Augustin (2020) [18] 13 -88,9 -Chang (2020) [20] 79 Метод щипцовой биопсии не является совершенным. Так, например, при неизменной внутренней стенке протока необходимо выполнять биопсию через слизистую оболочку, что ухудшает результаты морфологического исследования [21].…”
Section: автор (год)unclassified
See 1 more Smart Citation
“…Postoperative rehabilitation is important for patients with trauma and strengthening nursing measures can improve the speed of recovery[ 6 ]. Thus, the comprehensive treatment and nursing protocols implemented in the rapid rehabilitation nursing model have been well-received by most patients.…”
Section: Introductionmentioning
confidence: 99%